Evaluating modelling methods for mobile crane lifting operations in South Africa - De Wet van Niekerk; Michiel Bekker (Journal of Construction Project Management and Innovation)
The successful completion of construction projects is dependent on safe and efficient crane operations. As modularized (off-site) construction is increasingly replacing traditional on-site activities, the evaluation of mobile crane lifting modelling should be evaluated. This paper investigates current modelling practices adopted and utilised by South African firms for the planning and/or designing of mobile crane lifting operations, the influencing factors affecting the choice of modelling methods by firms, and the impact they have on project performance. Quantitative data gathered revealed that firms who are actively adopting virtual modelling as a planning tool for mobile crane lifting operations, have higher success rates with regards to achieving targeted project performance measures such as scheduling-, safety-, and achieving customer satisfaction goals. The research revealed that the two most significant factors influencing the choice of firms to adopt virtual modelling as a planning tool, was found to be Awareness and Perceived usefulness. Findings from the research suggest that failure to adopt innovation in this field could have long term negative consequences to the market share of firms operating within this industry. It is therefore suggested that South African firms within the lifting industry improve their competitiveness by ensuring they invest in the adoption of virtual modelling as a planning tool for mobile crane lifting operations.